2009
DOI: 10.1590/s0102-67202009000400004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polydextrose increases calcium absorption in normal rats

Abstract: BACKGROUND: Gastric surgery is known to cause bone disorders, possibly related to an impaired capacity for the absorption of dietary calcium. AIM: To verify if polydextrose (PDX) could stimulate calcium absorption in partially gastrectomized and sham operated rats. METHODS: The rats were laparotomized (sham-operated control) or partially gastrectomized (Billroth II), in groups of 20 each. Half in each operated group were fed a control diet (AIN-93M) without PDX or the same diet containing (PDX 50g/Kg of diet) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…46 The addition of a specific mixture of 0.6 g/100 mL of scGOS and lcFOS in a ratio of 9/1 to infant formula did not decrease cholesterol concentrations, although the levels in formula fed infants were significantly lower than in breast-fed infants. 47 Early prebiotic supplementation may alleviate symptoms associated with crying and fussing in preterm infants.…”
Section: Prebiotics and Stool Consistencymentioning
confidence: 86%
“…46 The addition of a specific mixture of 0.6 g/100 mL of scGOS and lcFOS in a ratio of 9/1 to infant formula did not decrease cholesterol concentrations, although the levels in formula fed infants were significantly lower than in breast-fed infants. 47 Early prebiotic supplementation may alleviate symptoms associated with crying and fussing in preterm infants.…”
Section: Prebiotics and Stool Consistencymentioning
confidence: 86%
“…PDX is a soluble fiber that could be fermented in the gut with production of short-chain fatty acids (SCFA) and reduction of pH. Several studies showed that PDX increases Ca absorption and retention [ 26 , 27 ]. Mineo et al [ 26 ] “in vitro” found that PDX enhances net Ca transport from the small and large intestine epithelium of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Mineo et al [ 26 ] “in vitro” found that PDX enhances net Ca transport from the small and large intestine epithelium of rats. Hara et al and dos Santos et al [ 4 , 27 ] demonstrated that the ingestion of PDX increases Ca absorption in normal and total gastrectomized rats suggesting that the small intestine rather than the large one is the responsible for Ca absorption increase. However, no studies were done to demonstrate PDX effect on OVX rats in which an extra Ca supplied may be relevant for avoiding bone mass diminution.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al [85] showed in a study to verify if polydextrose could stimulate calcium absorption in partially gastrectomized and sham operated rats that the polydextrose feeding (50 g/kg of diet) increased calcium absorption and bone calcium concentration in normal rats and the partially gastrectomy did not affect the bone calcium concentration. In a recent study, Santos et al [86] investigated whether polydextrose stimulates iron absorption in rats submitted to partial gastrectomy and sham operated and the diet with polydextrose reduced the excretion of iron and apparent iron absorption was higher in the polydextrose fed groups than in the control group.…”
Section: Polydextrose (Pdx)mentioning
confidence: 99%